ANALISIS NON VALUE ADDED ACTIVITY MELALUI PENERAPAN ACTIVITY BASED MANAGEMENT UNTUK MENINGKATKAN EFISIENSI PT. INDOFOOD CBP SUKSES MAKMUR, Tbk CABANG BITUNG - Kutika, Reika Fichristika; Saerang, David P. E.; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2018)
Nowadays, the changes that occur in the business environment creates competitiveness between companies in terms of seizing the market. For these companies, one of the way to achieve excellence is by being constantly focused on improving their processes and activities, paying attention to quality, flexibility and cost efficiency. Along with the competition of manufacturing companies that occur these days, PT. Indofood CBP Sukses Makmur, Tbk Bitung Branch must be able to manage its activities effectively and efficiently in order to achieve competitive advantage. Ergo, what companies need to do to improve its efficiency is by managing the activities that occur without reducing the quality of their products provided to customers. This study aims to find out how the application of activity based management at PT. Indofood CBP Sukses Makmur, Tbk Bitung Branch and how non value added activity can improve the efficiency of the company. The data analyze used descriptive analysis with qualitative approach and activity based management method. Based on the research, it is indicated that some non value-added activities are still going on, and by applying the activity-based management method, there is no added-value by the company’s reduction cost. By using activity-based management method, the total overhead cost of the factory is reduced by Rp 2,384,750,669,84 or 20,30%.Keyword: Activity Based Management, Non Value Added Activity, Efficiency